Reflective practice of experiential learning visit to drug rehabilitation centres improved pharmacy curriculum prospects and services in promoting community engagement - Mohd Taufek, Nor Hidayah; Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz; Zaini, Syahrir; Turner, Christopher John (IIUM Press, 2022)
Introduction: Reflective practice has been proven effective in improving students' learning outcomes from various health disciplines, including pharmacy. As healthcare providers, pharmacists have frequent contact with vulnerable patients with risky behaviours thus require appropriate attitudes and positive perceptions to ensure equal services. These intangible components require self-reflection of individual learning processes. This study aimed to investigate the view of pharmacy students towards an experiential learning opportunity at drug rehabilitation centres via a reflective practice approach.